Crítica imanente e a normatividade da performance - Alves, Ítalo Da Silva (2022)
In this study, I discuss the role of non-discursive practices in a project of immanent social critique, paying special attention to the issue of the normative-claiming capacity of these practices. My central question is whether it is possible to identify normative-claiming capacity in the nondiscursive aspect of social practices. My hypothesis is positive. I argue that the symbolic, ritualistic, aesthetic, or—under the specific focus of this study—performative aspect of social practices not only expresses socially established norms of action but also reacts to them, and is therefore capable of raising normative claims. Employing the method of literature research, the study reconstructs the methodological categories of “practice-based immanent critique” and “normative reconstruction” from the works of contemporary critical theorists Jürgen Habermas and Axel Honneth, pointing out their limits in theorizing performative aspects of action. The study offers a contribution to the question concerning the object of social critique from the field of performance studies, especially from the work of Erving Goffman.